OPPORTUNITIES OF BIOMEDICAL USE OF CARBON NANOTUBES - I. V. Mitrofanova; I. V. Milto; I. V. Suhodolo; G. Yu. Vasyukov (Бюллетень сибирской медицины, 2014)
Nanomaterials  –  materials,  whouse  structure  elements  has  proportions  doesn’t  exceed  100  nm.  In superdispersed state matter acquire new properties. In the last decade, carbon nanotubes become the most popular nanomaterials, that cause attention of representatives of various scientific field. The сarbon nanotubes offer new opportunities for biological and medical applications: imaging at the molecular, cellular and tissue levels, biosensors and electrodes based on carbon nanotubes, target delivery of various substances, radiation and photothermal therapy. The most promising of carbon nanotubes in the context of biomedical applications is their ability to penetrate the various tissues of the body and carry large doses of agents, providing diagnostic and therapeutic effects. Functionalized nanotubes are biodegradable. Other current direction of using carbon nanotubes in medicine and biology is to visualize objects on the molecular, cellular and tissue level. Associated with carbon nanotubes contrasting substances improve the visualization of cells and tissues, which can detected new patterns of development of the pathological process. Due to the vagueness of the question of biocompatibility and cytotoxicity of carbon nanotubes possibility of their practical application is hampered. Before the introduction of carbon nanotubes into practical health care is necessary to provide all the possible consequences of using nanotubes. High rates of properties and development of new nanostructures based on carbon nanotubes in the near future will lead to new advances related to the application and development of new parameters that will determine their properties and effects. In these review attention is paid to the structure, physico-chemical properties of nanotubes, their functionalization, pharmacokinetics and pharmacodynamics and all aspects of using of carbon nanotubes.